State Responsibility in Protecting Students in Overseas Internship Programs from Human Trafficking: A Critical Analysis of Regulatory Gaps After the Ferienjob Case - Farhan Muhammad Ramadhan; Rasji (Al-Risalah, 2026)
This study aims to analyze state responsibility in protecting international internship students from human trafficking practices, particularly following the Ferienjob case involving thousands of Indonesian students. The research employs a normative juridical approach with analysis of legislation related to overseas citizen protection, the Merdeka Belajar Kampus Merdeka (MBKM) policy, and international legal instruments on human trafficking. The findings reveal significant regulatory gaps in the supervision of overseas internship programs, weak verification mechanisms for organizing institutions, and unclear division of responsibilities among central government, universities, and program organizers. The study concludes that the state has legal obligations to provide preventive protection through strict regulation of MBKM-based internship programs, strengthening risk-based supervision systems, and imposing firm sanctions against organizers proven to exploit students as victims of human trafficking.